Simultaneous column preconcentration of ultra trace amounts of heavy metals with nano-adsorbent in some environmental and biological samples - Fazelirad, Hamid (Environmental technology, 2016)
In the present investigation, multi-walled carbon nanotubes impregnated by 1,4,10,13-tetraoxa-7,16-diazacyclooctadecane were prepared and applied as adsorbent for the simultaneous separation of Bi(III), Cu(II), Cd(II) and Pb(II) ions prior to their determination by electrothermal atomic absorption spectrometry. The following analytical figures of merit were determined for bismuth, copper, cadmium and lead, respectively: enrichment factors of 168, 134, 111 and 146, assay precisions of ±4.6%, ±4.8%, ±5.3% and ±5.0% and detection limits of 11.3, 3.7, 0.5 and 0.3 ng L(-1). The method was successfully applied for the determination of heavy metals in environmental, biological and certified reference materials